2013
DOI: 10.1016/j.joca.2013.02.605
|View full text |Cite
|
Sign up to set email alerts
|

Adjudication process for joint events of interest in fulranumab clinical trial program

Abstract: has been postulated that RAR antagonists may prevent or reverse retinoid-mediated cartilage destruction and a RAR pan antagonist was previously shown to improve clinical scores in the collagen-induced arthritis (CIA) model, albeit with unacceptable adverse effects on testes. We have postulated that the primary beneficial joint effects of RAR antagonists are associated with RARgamma, while the adverse effects on testes are associated with RARalpha. Thus, we have identified a highly selective RARgamma antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…All cases of RPOA in the current study, irrespective of whether these were in the target joint, appeared to be associated with combination therapy with fulranumab and NSAIDs in patients with preexisting OA, which is consistent with previous findings . Published studies have also demonstrated an increased risk of RPOA for the combination of tanezumab and a long‐term NSAID as compared with tanezumab monotherapy .…”
Section: Discussionsupporting
confidence: 91%
“…All cases of RPOA in the current study, irrespective of whether these were in the target joint, appeared to be associated with combination therapy with fulranumab and NSAIDs in patients with preexisting OA, which is consistent with previous findings . Published studies have also demonstrated an increased risk of RPOA for the combination of tanezumab and a long‐term NSAID as compared with tanezumab monotherapy .…”
Section: Discussionsupporting
confidence: 91%
“…The methods and results of the adjudication process and its implications for the further clinical development of tanezumab were presented at a meeting of the U.S. FDA held in March 2012 17 and at the 2012 annual meeting of the American College of Rheumatology 18 and will be summarized briefly in this manuscript. In addition, this manuscript also will summarize briefly the methods and results of a similar process conducted by Janssen Research and Development, LLC for cases reported during the clinical development program for fulranumab that were presented at the same 2012 meeting of the U.S. FDA 19 and at the 2013 annual meeting of the Osteoarthritis Research Society International 20 . It should be noted that different adjudication committees were used by the different companies.…”
mentioning
confidence: 99%